PENGARUH KEWAJIBAN PELANGGAN, KEMAUAN MEMBAYAR DAN SANKSI DENDA KEPADA PELANGGAN TERHADAP KEPATUHAN PEMBAYARAN REKENING LISTRIK PADA PT PLN (PERSERO) KABUPATEN OGAN KOMERING ULU - Hema Malini; Eva Ria Indriani (STIE DWI SAKTI BATURAJA, 2021)
The purpose of this study was to determine the effect of customer obligations, willingness to pay and penalty sanctions to customers on compliance with electricity account payments at PT PLN (Persero), Ogan Komering Ulu Regency. This research is a descriptive study and using incidental sampling with a sample size of 91 respondents. Using multiple regression analysis techniques and to test the research hypothesis used, the F-test and t test. From the calculation results, it is found that; 1) The coefficient value of Customer Liability (X1) is (0.182), 2) The coefficient of Willingness to Pay (X2) is (0.236), 3) The coefficient of Penalty on Customers (X3) is (0.470), this means Customer Liability, Willingness Paying and Penalties on Customers affect the Compliance of Electricity Account Payments by customers. From the results of the t test hypothesis, the following results are obtained; 1) The value of tcount of customer obligations (X1) (1,438) <ttabel (1,987) means that there is no influence of Customer Liabilities on Electricity Account Payment Compliance, 2) The value of tcount of willingness to pay (X2) is (1,713) <ttabel (1,987) means that there is no the effect of Willingness to Pay on Compliance with Electricity Account Payments, 3) The value of tcount of fines to customers (X3) is (4,270)> t table (1,987) which means that there is an effect of Fines on Customers of Compliance with Electricity Account Payment. Meanwhile, from the results of the hypothesis test, it is found that the value of Fcount (33.309)> Ftable (2.71), this means that the variables of Customer Liability, Willingness to Pay and Penalties to Customers together have a significant effect on Compliance of Electricity Account Payments by customers on PT PLN (Persero) Ogan Komering Ulu Regency.